Bleomycin Induced Sensitivity to TRAIL/Apo-2L-Mediated Apoptosis in Human Seminomatous Testicular Cancer Cells is Correlated with Upregulation of Death Receptors - Timur, Mujgan; Cort, Aysegul; Ozdemir, Evrim; Bilmen Sarikcioglu, Sureyya; Sanlioglu, Salih; Dilsad Sanlioglu, Ahter; Ozben, Tomris (Anti-Cancer Agents in Medicinal Chemistry, 2015)
The most common solid tumor is testicular cancer among young men. Bleomycin is an antitumor antibiotic used for the therapy of testicular cancer. TRAIL is a proapoptotic cytokine that qualified as an apoptosis inducer in cancer cells. Killing cancer cells selectively via apoptosis induction is an encouraging therapeutic strategy in clinical settings. Combination of TRAIL with chemotherapeutics has been reported to enhance TRAIL-mediated apoptosis of different kinds of cancer cell lines. The molecular ground for sensitization of tumour cells to TRAIL by chemotherapeutics might involve upregulation of TRAIL-R1 (TR/1, DR4) and/or TRAIL-R2 (TR/2, DR5) receptors or activation of proapoptotic proteins including caspases. The curative potential of TRAIL to eradicate cancer cells selectively in testicular cancer has not been studied before. In this study, we investigated apoptotic effects of bleomycin, TRAIL, and their combined application in NTera-2 and NCCIT testicular cancer cell lines. We measured caspase 3 levels as an apoptosis indicator, and TRAIL receptor expressions using flow cytometry. Both NTera-2 and NCCIT cells were fairly resistant to TRAIL’s apoptotic effect. Incubation of bleomycin alone caused a significant increase in caspase 3 activity in NCCIT. Combined incubation with bleomycin and TRAIL lead to elevated caspase 3 activity in Ntera-2. Exposure to 72 h of bleomycin increased TR/1, TR/2, and TR/3 cell-surface expressions in NTera-2. Elevation in TR/1 cell-surface expression was evident only at 24 h of bleomycin application in NCCIT. It can be concluded that TRAIL death receptor expressions in particular are increased in testicular cancer cells via bleomycin treatment, and TRAIL-induced apoptosis is initiated.
Keywords: caspase-3